Voluntary disclosure by Shariah approved companies: an exploratory study - Ousama, Abdulrahman Anam; Abdul Hamid, Fatima (Emerald Group Publishing Limited, 2010)
The purpose of this paper is to investigate the extent of voluntary disclosure (EVD)(i.e. overall, conventional, and Islamic disclosure) in the annual reports of Shariah Approved Companies (ShAC) listed on Bursa Malaysia.